Acetylcholine induces fibrogenic effects via M2/M3 acetylcholine receptors in non‐alcoholic steatohepatitis and in primary human hepatic stellate cells. Issue 2 (28th January 2016) - Morgan, Maelle L; Sigala, Barbara; Soeda, Junpei; Cordero, Paul; Nguyen, Vi; McKee, Chad; Mouraliderane, Angelina; Vinciguerra, Manlio; Oben, Jude A
Abstract: Background: The parasympathetic nervous system (PNS), via neurotransmitter acetylcholine (ACh), modulates fibrogenesis in animal models. However, the role of ACh in human hepatic fibrogenesis is unclear. Aims: We aimed to determine the fibrogenic responses of human hepatic stellate cells (hHSC) to ACh and the relevance of the PNS in hepatic fibrosis in patients with non‐alcoholic steatohepatitis (NASH). Methods: Primary hHSC were analyzed for synthesis of endogenous ACh and acetylcholinesterase and gene expression of choline acetyltransferase and muscarinic ACh receptors (mAChR). Cell proliferation and fibrogenic markers were analyzed in hHSC exposed to ACh, atropine, mecamylamine, methoctramine, and 4‐diphenylacetoxy‐ N ‐methylpiperidine methiodide. mAChR expression was analyzed in human NASH scored for fibrosis. Results: We observed that hHSC synthesize ACh and acetylcholinesterase and express choline acetyltransferase and M1–M5 mAChR. We also show that M2 was increased during NASH progression, while both M2 and M3 were found upregulated in activated hHSC. Furthermore, endogenous ACh is required for hHSC basal growth. Exogenous ACh resulted in hHSC hyperproliferation via mAChR and phosphoinositide 3‐kinase and Mitogen‐activated protein kinase kinase (MEK) signaling pathways, as well as increased fibrogenic markers. Conclusion: We show that ACh regulates hHSC activation via M2 and M3 mAChR involving the phosphoinositide 3‐kinase and MEK pathways in vitro . Finally, we provide evidence that the PNS may be involved in human NASH fibrosis.